A model for ripple effects analysis of cascading problems in ontology evolution. (1st January 2012) - Sall, Ousmane; Thiam, Mouhamadou; Bousso, Mamadou; Lo, Moussa; Basson, Henri
Ontology engineering is one of semantic web's most important activities. Inconsistencies observed on cascading changes of nodes would arise simply as result of any small operation on an ontology component. It is therefore necessary to have tools to evaluate consequent flows on other components as result of an operation on ontology. In this paper, we present an approach that provides an algorithm and a support for ripple effects analysis of cascading problems in ontology evolution by derivation of changes based on corresponding pre-conditions, post-conditions and invariants.